2000
DOI: 10.1021/np990313b
|View full text |Cite
|
Sign up to set email alerts
|

Production and Structure Elucidation of Glycoglycerolipids from a Marine Sponge-Associated Microbacterium Species

Abstract: The bacterium Microbacterium sp., isolated from the sponge Halichondria panicea, produced four unusual cell-associated glycoglycerolipids and one diphosphatidylglycerol when grown on marine broth and on artificial seawater media. The lipids were isolated by chromatography on silica columns and their structures elucidated using a combination of multidimensional NMR and MS techniques. The main compound was 1-O-acyl-3-[alpha-glucopyranosyl-(1-3)-(6-O-acyl-alpha-mannopyranosyl )]glycerol (GGL.2) with 14-methyl-hex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…strain HP2, which was isolated from a Antimicrobial activities were determined as inhibition zones (in mm) measured from the edge of the disc after 24 h of incubation. The bacteria used in this experiment are: S. aur-Staphylococcus aureus, S. epi-Staphylococcus epidermidis, S. mar-Serratia marcescens, K. pneKlebsiella pneumonia, S. typ-Salmonella typhi, S. ent-Salmonella entertidis a Mediterranean sponge Halichondria panicea, was able to synthesize a new glucosyl-mannosyl-glycerolipid, an antitumor agent (Wicke et al 2000). The reason for the low activity of strains is possibly due to the fact that these pathogenic bacteria are not natural competitors for the epibiotic bacteria and therefore lack a secondary metabolite that would induce the antimicrobial activity.…”
Section: Resultsmentioning
confidence: 99%
“…strain HP2, which was isolated from a Antimicrobial activities were determined as inhibition zones (in mm) measured from the edge of the disc after 24 h of incubation. The bacteria used in this experiment are: S. aur-Staphylococcus aureus, S. epi-Staphylococcus epidermidis, S. mar-Serratia marcescens, K. pneKlebsiella pneumonia, S. typ-Salmonella typhi, S. ent-Salmonella entertidis a Mediterranean sponge Halichondria panicea, was able to synthesize a new glucosyl-mannosyl-glycerolipid, an antitumor agent (Wicke et al 2000). The reason for the low activity of strains is possibly due to the fact that these pathogenic bacteria are not natural competitors for the epibiotic bacteria and therefore lack a secondary metabolite that would induce the antimicrobial activity.…”
Section: Resultsmentioning
confidence: 99%
“…The low sequence similarity and phylogenetic analysis suggested that it might belong to a novel taxon. Some genera, to which the novel isolates belong, are well-known and prolific metabolite producers (Iwatsuki et al 2006;Wicke et al 2000). The novel strain may produce a number of commercially interesting and potentially useful products.…”
Section: Discussionmentioning
confidence: 99%
“…(260), while a glycoglycerolipid produced by a Halichondria panicea-derived Microbacterium sp. had antitumor properties (463). In another study, several quinolones, including one with both antimicrobial and cytotoxic activities, were isolated from a pseudomonad from the Pacific sponge Homophymia sp.…”
Section: Methods For Accessing the Hidden Chemistry Of Marine Spongesmentioning
confidence: 99%